Early days of APC resistance and FV Leiden - Dahlbäck, B. (Hämostaseologie, 2008)
Venous thrombosis is a major medical problem annually affecting millions of individuals worldwide. It is a typical multifactorial disease, the pathogenesis involving both environmental and genetic risk factors. A single point mutation in the gene of coagulation factor V (FV), which results in the replacement of Arg506 with a Gln (FV Leiden) is the most common genetic risk factor known to date. The anti - coagulant activated protein C (APC) regulates the activity of FVa by cleaving several sites in FVa, and the Arg506 is one of them. APC resistance, which is the consequence of the FV Arg506Gln mutation, results a lifelong hypercoagulable state that increases the risk of thrombosis. APC resistance was discovered in my laboratory and the first paper was published in 1993. This was the starting point for an avalanche of research in many laboratories and several thousands of articles have been published since on this topic. The medical community amazingly quickly accepted the concept of APC resistance/FV Leiden as a major risk factor for thrombosis and millions of individuals are today tested for this condition. This review is a personal historical annotation about the early days of APC resistance.
Keywords: Protein C; factor V; factor V Leiden; FV Leiden; thrombophilia; thrombosis; APC resistance